Mechanistic insights into Jianpi Qinghua Sanyu Yin treatment of raised erosive gastritis: ceRNA-mediated PI3K/AKT signaling pathways - Liu, Liya; Cheng, Ying; Lin, Guosheng; Zheng, Huifang; Zhang, Xinran; Zhao, Peilin; Guo, Meixuan; Liu, Qihong; Fang, Wenyi; Wang, Wenrong; Jafri, Anjum; Shen, Aling; et al. (Frontiers in Pharmacology, 2025)
BackgroundRaised erosive gastritis (REG) is a chronic gastritis with a high risk of malignant transformation. Current treatments often result in high recurrence rates and complications. Jianpi Qinghua Sanyu Yin (JPQHSYY), a traditional Chinese medicine, shows promise in treating REG. However, the underlying molecular mechanisms remain unclear. This study aimed to investigate the potential mechanism of JPQHSYY’s therapeutic effects on REG.MethodsRNA-seq was employed to systematically analyze mRNA, lncRNA, and miRNA profiles in gastric mucosal tissues from REG patients before and after JPQHSYY treatment. The pivotal lncRNA-miRNA and miRNA-mRNA networks were predicted from sequencing data and bioinformatic analysis, and the results were exported using Cytoscape software. Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were used for functional exploration. Real-time quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was performed to validate RNA-seq analysis results. CCK8, cell cycle, apoptosis and western blot were performed to detect the effects of miR-122-5p in GES-1 cells in vitro.ResultsRNA-seq analysis revealed 576 differentially expressed lncRNAs (269 upregulated, 307 downregulated), 33 differentially expressed miRNAs (13 upregulated, 20 downregulated), and 1717 differentially expressed mRNAs (777 upregulated, 940 downregulated) in JPQHSYY-treated REG patients. GO and KEGG analyses highlighted key pathways, including the PI3K/AKT signaling pathway, involved in cell cycle and apoptosis regulation. The ceRNA network analysis suggested that JPQHSYY impacts the miRNA–lncRNA interactions. Validation experiments confirmed that JPQHSYY inhibits the PI3K/AKT pathway, reducing cell viability, colony formation, and promoting apoptosis in miR-122-5p transfected GES-1 cells.ConclusionThe therapeutic efficacy of JPQHSYY in treating REG might be mediated by the ceRNA-driven PI3K/AKT pathway signaling pathways, which is implicated in the proliferation of gastric mucosal epithelial cells. Furthermore, the investigation of miRNA–lncRNA networks could reveal more information on potential new mechanisms and targets for JPQHSYY in the management of REG.